Effectiveness of horizontal and vertical constructed wetlands performance systems with some vegetation on domestic waste concentrations - Harahap, Azmi wijayanti; Rosmayati, Rosmayati; Rahmawati, Nini (Institute of Computer Science (IOCS), 2023)
Population growth has resulted in the demand for waste water reclamation increasing rapidly. CW systems are an inexpensive technology with little or no energy requirements and very minimal equipment requirements, resulting in low construction costs. This research will test improving the quality of domestic wastewater using a Vertical Flow Artificial Wetland (VFCW) and Horizontal Flow Artificial Wetland (HFCW) system using kangkong, water hyacinth and lotus vegetation. The results of the research carried out can be concluded as follows: in water spinach vegetation there is no difference in the concentration of BOD, COD, DO, Oil and Fat, Detergent, Ammonia, and total coliform parameters of the horizontal CW type and the vertical CW type. In water hyacinth vegetation there were no differences in the concentrations of BOD, COD, DO, Oil and Fat, Detergent, Ammonia, and total coliform parameters of the horizontal CW type and vertical CW type. In lotus vergetation there were no differences in the concentration of BOD, COD, DO, Oil and Fat, Detergent, Ammonia, and total coliform parameters of the horizontal CW type and vertical CW type. In the research results, there is no significant difference in the horizontal CW and vertical CW types in improving water quality, especially domestic waste, you can use horizontal CW or vertical CW types.